2018
DOI: 10.3390/geosciences9010003
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Geochemical Investigation down to 2000 m Deep Triassic Rock (Meuse/Haute Marne, France)

Abstract: In 2008, as part of a feasibility study for radioactive waste disposal in deep geological formations, the French National Radioactive Waste Management Agency (ANDRA) drilled several boreholes in the transposition zone in order to define the potential variations in the properties of the Callovo-Oxfordian claystone formation. This consisted of a rare opportunity to investigate the deep continental biosphere that is still poorly known. Four rock cores, from 1709, 1804, 1865, and 1935 m below land surface, were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…There is a reasonable chance that the extremophilic microbial population belonging to Cyclobacteriaceae and Rhodobacteriaceaeae might have become enriched in the DFs sampled at lower depths due to the extreme conditions (Zhang et al, 2006;Kumar et al, 2012). Alternatively, it could also be concluded that they might be part of the deep subsurface microbiome (Russell et al, 2016;Hubalek et al, 2016;Leboulanger et al, 2017). Subsequently the relative abundance of some of the microbial families, known to strive in strictly anaerobic and extremophilic environments (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is a reasonable chance that the extremophilic microbial population belonging to Cyclobacteriaceae and Rhodobacteriaceaeae might have become enriched in the DFs sampled at lower depths due to the extreme conditions (Zhang et al, 2006;Kumar et al, 2012). Alternatively, it could also be concluded that they might be part of the deep subsurface microbiome (Russell et al, 2016;Hubalek et al, 2016;Leboulanger et al, 2017). Subsequently the relative abundance of some of the microbial families, known to strive in strictly anaerobic and extremophilic environments (e.g.…”
Section: Discussionmentioning
confidence: 99%